Integrasi Nilai SDGS dan Pancasila: Strategi Indonesia Mewujudkan Pertumbuhan Ekonomi Inklusif di Daerah - Zahira Nandhifa Syifarany; Fawnia Azalia Sekar Parahita; Febby Cipta; Moh Hardy Yulinar Firdaus; Nauval Dzikri Gofari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine how Indonesia is implementing the Pancasila economic system to help accomplish the Sustainable Development Goals (SDGs) at the national and regional levels. It uses a descriptive qualitative technique to look at both external and internal issues, such as global economic conditions, maritime security, human resources, natural resources, sociocultural dynamics, politics, and government functions. Regional case studies of the Pancasila economic system's implementation in Maluku Province, Papua Province, Sukabumi Regency, and Sulawesi Island are also included in the study. The results show that inclusive and fair economic development has been reinforced throughout areas by the application of Pancasila values, such as social justice and cooperation. The productive-age population makes up 70.7% of the population while the agricultural sector provides 12.53% of GDP, according to Statistics Indonesia (BPS, 2025). Persistent inequality is highlighted by a Gini value of 0.375. According to the study's findings, the Pancasila economic system and the SDGs may work together to promote inclusive, socially just, and sustainable national growth.